Reduced graphene oxide wrapped sulfur nanocomposite as cathode material for lithium sulfur battery. Issue 10 (15th May 2021) - Shastri, Mahesh; Shetty, Manjunath; Rani M, Navya; Muniyappa, Murthy; Sree, Muralidhar Sindhu; Gangaraju, Vinay; Sabanhalli, Chethan; Lokesh, S.V.; Shivaramu, Prasanna D.; Rangappa, Dinesh
Abstract: Sulfur has been investigated as an active electrode material for secondary batteries due to theoretically specific capacity compared to the lithium-ion battery. In the present study, reduced graphene oxide (RGO) sheets wrapped Sulfur nanocomposite (S-RGO) synthesized by hydrothermal method and confirmed the wrapping of RGO sheets on Sulfur nanoparticles by various analytical techniques. The synthesized S-RGO nanocomposite demonstrated improved interaction of sulfur nanoparticles with RGO which is confirmed through XPS analysis. The synthesized S-RGO resulted in significantly improved reversible specific capacity and higher rate capability (823 mAh/g at 0.1C, 400 mAh/g at 1C) with 77 wt% of sulfur loading amount on the cathode of the Li–S battery. Therefore, the present study opens up new insights into sustainable development in the field of Li–S battery energy storage applications.